2003
DOI: 10.1029/2003gl016951
|View full text |Cite
|
Sign up to set email alerts
|

Determining pore‐throat size in Permo‐Triassic sandstones from low‐frequency electrical spectroscopy

Abstract: [1] Hydraulic conductivity or permeability, a knowledge of which is vital in modelling the movement of hydrocarbons in reservoir rocks and contaminants in aquifers, is strongly related to the intergranular pore-throat size in sandstones. For many years attempts have been made to determine permeability from the electrical properties of rocks, but with little success. Here we have measured the complex electrical conductivity of PermoTriassic sandstone samples over the frequency range 0.0001 -1000 Hz and show how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 18 publications
5
94
0
Order By: Relevance
“…Most recently, it has been shown that there are strong relationships between the spectral resistivity parameters and the pore-size distribution obtained using mercury injection capillary pressure instruments (Scott & Barker 2003. This opens up the possibility of estimation of permeability, using both surfacebased and borehole-based resistivity measurements.…”
Section: Geophysical Estimation O F Hydraulic Propertiesmentioning
confidence: 99%
“…Most recently, it has been shown that there are strong relationships between the spectral resistivity parameters and the pore-size distribution obtained using mercury injection capillary pressure instruments (Scott & Barker 2003. This opens up the possibility of estimation of permeability, using both surfacebased and borehole-based resistivity measurements.…”
Section: Geophysical Estimation O F Hydraulic Propertiesmentioning
confidence: 99%
“…The characteristic length scale is dependent on microgeometrical characteristics, for example the main grain or pore size in the material (e.g. Scott & Barker 2003, Binley et al 2005. A wider distribution of length scales generally leads to a lower frequency factor (and a less pronounced drop in the polarization at the relaxation time).…”
Section: Data Processing and Inversionmentioning
confidence: 99%
“…However, most petrophysical relationships between spectral IP and rock properties have been derived using parameters describing the microgeometry of sandstones, for example pore throat distribution and dominant pore throat size (see e.g. Scott & Barker 2003;Binley et al 2005). Since the microstructure of limestones differs from sandstones, a microscale investigation of samples from the Kristianstad limestone was performed in order to give an insight into the microstructure and composition of the investigated rock type.…”
mentioning
confidence: 99%
“…Importantly, for both polarization mechanisms, the observed time scale of relaxation, as quantified by the Cole-Cole time constant τ, is directly related to the length scale determined by the size of electronically conducting grains in mineralized rock (Pelton et al, 1978) or by the length scale characteristic of the pore space in sedimentary rock (e.g., Titov et al, 2002;Scott and Barker, 2003;Binley et al, 2005;Slater, 2007). In this sense, the measured complex resistivity spectrum represents an integrated response over all length scales presented in the rock (e.g., Leroy et al, 2008).…”
Section: Cole-cole Modelmentioning
confidence: 99%